Determinants of key success criteria in establishing and sustaining an Internet of Things (IOT) new technology venture (NTV) in South Africa - Suleman, Hussain (My University, 2016)
Technology entrepreneurship is vital to economic development as it could have positive effects on employment and could rejuvenate industries, especially through disruptive technologies. Studies have shown that South Africa has one of the highest new venture failure rates across the globe and it is, therefore, becoming critical to determine the key factors of successful technology ventures that could contribute to sustaining new technology ventures in South Africa. With the Internet of Things (IoT) fast becoming the most exciting technology trend aimed at transforming everyday business and individual lives, this study set out to investigate the key success criteria for IoT new ventures, as well as key sectors for IoT within South Africa. Linking technology entrepreneurship and the opportunities provided by IoT, this research aims to identify the key success criteria of entrepreneurial ventures within South Africa, as well as analyse the South African IoT ecosystem to determine which sectors provide the greatest opportunity for technology entrepreneurs. This research was conducted through primary research across IoT new technology ventures, as well as enterprises across industries within South Africa. The study found that successful ventures and unsuccessful ventures have different entrepreneur characteristics. A key characteristic for successful IoT ventures is entrepreneur ambitions, while education is the biggest hindrance to unsuccessful ventures. The related car and fleet management industries were found to provide the largest opportunity for IoT entrepreneurship in South Africa. This study provides valuable insight into the IoT market that will aid the sustainability of IoT entrepreneurship. From an academic perspective, it supplements the existing literature on technology and IoT entrepreneurship in South Africa.
A RESEARCH REPORT SUBMITTED TO THE FACULTY OF COMMERCE, LAW AND MANAGEMENT, UNIVERSITY OF THE WITWATERSRAND, IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF MASTER OF MANAGEMENT SPECIALISING IN ENTREPRENEURSHIP AND NEW VENTURE CREATION Johannesburg, 2016
Keywords: Entrepreneurship--South Africa; New business ventures--South Africa; Internet of Things; Ubiquitous computing